Evaluation of the need for suspension of new oral anticoagulants to perform dental extractions: systematic review (Research, Society and Development, 2023)
Objective: This systematic review aimed to analyze the need to suspend or not the uso of new oral anticoagulants (NOACs) during dental extractions. Materials and Methods: For this systematic review, the PRISMA-2020 criteria were used, structured in the question "What is the approach to be adopted by dental surgeons for individuals using new oral anticoagulants and who need oral exemptions?". The selection of articles were based on the search strategy "PICO", developed for the electronic databases Cochrane Central Register of Controlled Trials (CENTRAL), Embase, Lilacs, Livivo, PubMed, Scopus and Web of Science. The selected articles presented patients using Apixabana, Dabigatrana, Edoxabana and Rivaroxaban. Those who met the election criteria were selected. Results: A total of 2,281 studies were found from the electronic databases. The studies selected for full reading were 100, of which 99 were discarded due to incompatibility with the inclusion criteria mentioned in the research in question. Finally, only 1 study article was included for the research. The assessment of the level of evidence identified a moderate risk of bias. Conclusions: Through the analysis of the selected study, which presented a moderate risk of bias, it was concluded that patients who use NOACs and will be submitted to tooth extractions do not need to suspend the use of these drugs, as long as the protocols are followed, specially the use of local hemostasis maneuvers and more recurrent postoperative control. It is suggested the suspension of NOACs in multiple extractions or in other situations where greater bleeding is expected.